2023
DOI: 10.1126/science.ade3332
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of mammalian respiratory complex I inhibition by medicinal biguanides

Abstract: The molecular mode of action of biguanides, including the drug metformin, which is widely used in the treatment of diabetes, is incompletely characterized. Here, we define the inhibitory drug-target interaction(s) of a model biguanide with mammalian respiratory complex I by combining cryo–electron microscopy and enzyme kinetics. We interpret these data to explain the selectivity of biguanide binding to different enzyme states. The primary inhibitory site is in an amphipathic region of the quinone-binding chann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 82 publications
0
57
0
Order By: Relevance
“…These contacts, the binding mode and the ligand internal conformation match those observed for rotenone bound at ROT2 in the cryoEM model of complex I in open state (PDBs 6ZKL and 6ZKM) 8 . Moreover, this corresponds to the binding site closest to the Q-channel central region also observed for the substrate Q-headgroup 6,12 and other amphiphilic molecules 23,25,26 .…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…These contacts, the binding mode and the ligand internal conformation match those observed for rotenone bound at ROT2 in the cryoEM model of complex I in open state (PDBs 6ZKL and 6ZKM) 8 . Moreover, this corresponds to the binding site closest to the Q-channel central region also observed for the substrate Q-headgroup 6,12 and other amphiphilic molecules 23,25,26 .…”
Section: Resultsmentioning
confidence: 53%
“…Compound IACS-2858, a derivative of IACS-010759 which is under clinical trials as an anticancer agent, binds with its oxadiazole and pyridone moieties in the hydrophilic central region and competitively inhibits complex I by a “cork-in-bottle” mechanism 23 . The biguanide IM1761092, a more hydrophobic and potent derivative of the widely used metformin antidiabetic drug, also binds in the Q-channel central region 25 . Even detergent molecules used for protein purification, such as n -dodecyl -D-maltoside (DDM), have been observed with their polar heads in the hydrophilic central region 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 2000s, mitochondria have been considered the classic target organelles for the glucose-lowering actions of metformin, based on matrix enrichment and the specific, mild and reversible inhibition of the mitochondrial respiratory chain complex I 26 . Remarkably, a study published in 2023 combining cryo-electron microscopy and enzyme kinetics identified three possible independent binding or interaction sites for biguanides on various complex I protein subunits 62 . The major inhibitory site is located in the amphipathic region of the quinone-binding channel (Q-channel), adjacent to a mobile structural element in the NDUFS7 subunit; when a biguanide binds to this site, reactivation of the enzymatic deactivated state is prevented 62 , as previously reported 63 .…”
Section: Paradigm Changes In Glucoregulatory Actionsmentioning
confidence: 99%
“…Remarkably, a study published in 2023 combining cryo-electron microscopy and enzyme kinetics identified three possible independent binding or interaction sites for biguanides on various complex I protein subunits 62 . The major inhibitory site is located in the amphipathic region of the quinone-binding channel (Q-channel), adjacent to a mobile structural element in the NDUFS7 subunit; when a biguanide binds to this site, reactivation of the enzymatic deactivated state is prevented 62 , as previously reported 63 . These structural data obtained using a synthetic biguanide-like molecule supports a specific effect on complex I.…”
Section: Paradigm Changes In Glucoregulatory Actionsmentioning
confidence: 99%